THE POSITION OF AMICUS CURIAE IN THE EVIDENTIARY PROCESS OF CRIMINAL CASES IN INDONESIA - I Made Bima Cahyadi; Faizin Sulistio; Bambang Sugiri (CV. RADJA PUBLIKA, 2025)
This study examines the role of Amicus Curiae in the Indonesian legal system, particularly its impact on judicial decision-making despite the absence of explicit procedural regulations in the Criminal Procedure Code (KUHAP). Through qualitative analysis of landmark cases, including the Prita Mulyasari case, this research highlights how third-party legal opinions contribute to more just and transparent verdicts. The study identifies key challenges, such as inconsistent acceptance and limited awareness among legal practitioners, while also exploring potential frameworks for institutionalizing Amicus Curiae in both criminal and civil cases. By analyzing comparative legal perspectives and best practices from other jurisdictions, this research advocates for clearer guidelines to enhance its legitimacy and effectiveness in Indonesia. The findings underscore the necessity of formal recognition to strengthen judicial credibility, ensure fairness, and uphold fundamental human rights. Ultimately, institutionalizing Amicus Curiae would foster a more inclusive and participatory legal system, aligning Indonesia’s judiciary with global standards of legal justice and due process.